Memutus Mata Rantai Radikalisme dan Terorisme Berbasis Studi Etnopedagogi di PTNU dalam Membentuk Keberagamaan Inklusif dan Pluralis - Mukhibat Mukhibat (Islamica: Jurnal Studi Keislaman, 2015)
Education, including Islamic education, is one the fundamental instruments for nation and character building. The heterogeneity and plurality of social interactions, horizontally and vertically, need inclusive, tolerant and multicultural educational instruments. The term ethnopedagogy constitutes appropriate and relevant instrument to be developed in education as social and cultural reconstruction. In the context of Nahdlatul Ulama university or higher educational instutution (PTNU), the study of ethnopedagogy needs to be considered as a part of curriculum reform to produce the generation with inclusive, humanist and pluralist religiosity. This process will establish a perspective rooted in the variety of local epistemological framework in order to avoid streams that decrease national identity. The importance of respecting religious identity and different local cultures becomes the keyword of learning processes which correspond to students? experiences related to their life. Accordingly, the lecturers of PTNU should explore more contextual processes in learning so that the articulation of Islamic teachings as the content of learning for guiding students? life will not be out of context. The study of ethnopedagogy in turn will be able to cope with radicalism and terrorism and to face against formalism of some Islamic educational institutions that teach the puritanism of the Middle East.